Pengaruh Pandemi Covid-19 Terhadap Rantai Pasok UMKM di Indonesia - Erika Sri Wahyuni; Khori Ayu Tridyanthi (Universitas Muhammadiyah Enrekang, 2022)
This study aims to narrate or inform readers about the influence of the UMKM supply chain in Indonesia during the Covid-19 pandemic. The type of research in this research is expanatory research with a quantitative approach. The research method used is the method of collecting data from various sources on the internet, by combining these sources into one. The data collection technique used is to find the required information. The results of this study indicate that the impact of the COVID-19 pandemic has made many sectors slump, including the UMKM sector. The impact of COVID-19 has damaged supply chains for MSMEs in Indonesia, especially due to the implementation of social restrictions.